K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

15 tháng 4 2016

bạn thế -25 vào x,y rồi tính

18 tháng 8 2023

18 - 4\(x\) = -20 - 6\(x\) 

-4\(x\) + 6\(x\) = - 20  - 18

      2\(x\)    = - 38

         \(x\)  = - 19

h, -15 \(\times\) 24 = -7\(x\) + 32

     7\(x\) = 360 + 32

      7\(x\) = 392

         \(x\) =  392:7

          \(x\) = 56

18 tháng 8 2023

i, 15\(x\) -3.(4\(x\) - 6) = -12 + 36

    15\(x\) - 12\(x\) + 18 =  24

      3\(x\) = 24 - 18

       3\(x\) = 6

         \(x\) = 2

k, -10\(x\) - 27 = -7\(x\) + 33

    -27 - 33 = -7\(x\) + 10\(x\)

     3\(x\) = -60

        \(x\) = -20

 

 

18 tháng 1 2018

33 - 23 + 3 = 13

1 tháng 5 2019

a, |3x - 6| + 4x + 3 = 12

|3x - 6| = 12 - 3 - 4x

|3x - 6| = 9 - 4x

TH1: 3x - 6 = 9 - 4x ⇔ 3x + 4x = 9 + 6 ⇔ 7x = 15 ⇔ x = 15/7 

TH2: 3x - 6 = 4x - 9 ⇔ 3x - 4x = -9 + 6 ⇔ -x = -3 ⇔ x = 3. 

b, |6x - 12| + 3x - 1 = 43

|6x - 12| = 43 + 1 - 3x

|6x - 12| = 44 - 3x

TH1: 6x - 12 = 44 - 3x ⇔ 6x + 3x = 44 + 12 ⇔ 9x = 56 ⇔ x = 6.

TH2: 6x - 12 = 3x - 44 ⇔ 6x - 3x = -44 + 12 ⇔ 3x = -32 ⇔ x = -32/3.

c, |8 - 4x| + 7x - 5 = 16 - 2x

|8 - 4x| = (16 + 5) + (-2x - 7x)

|8 - 4x| = 21 - 9x

TH1: 8 - 4x = 21 - 9x ⇔ -4x + 9x = 21 - 8 ⇔ 5x = 13 ⇔ x = 13/5

TH2: 8 - 4x = 9x - 21 ⇔ -4x - 9x = -21 - 8 ⇔ -15x = -29 ⇔ x = 29/15

⇔(2 x ) 2+2.2 x .1+1 2=0 ... c ,(3 x −42−14(3 x −4)(6+3 x )+49(3 x +6)=16 ... ⇔9 x 224 x +16−126 x 2252 x +168 x +336+147 x +294=16.

https://olm.vn/hoi-dap/detail/192758180810.html

12 tháng 2 2020

5x-16=40+x

=> 5x-16-x = 40

=> 5x-x -16=40

4x-16=40

4x= 40+16

4x=56

x= 56:4

x=14

Vậy...

12 tháng 2 2020

4x-10=15-x

=> 4x-10+x= 15

4x+x -10=15

5x= 15+10

5x= 25

x= 25:5

x=5

Vậy....